EXPLORING THE COLLECTIVE UNCONSCIOUS: JUNGIAN ARCHETYPES IN ARAVIND ADIGA’S THE WHITE TIGER - Khare, Somya; Purwar, Pratima (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the Archetypal dimensions of Aravind Adiga’s novel The White Tiger and its cinematic adaptation through the lens of Carl Jung’s Archetypal theory. Focusing on the archetypes of the Hero and Antihero, The Trickster, and The Shadow, the research examines how Balram Halwai’s transformation embodies the paradox of heroism and moral ambiguity. By analysing Balram’s journey from servitude to self-liberation, the study interrogates his dual role as both a heroic liberator and a morally transgressed antihero. The trickster archetype, symbolized in Balram’s cunning and deception, is evaluated in the context of his navigation through India’s socio-economic hierarchies, exposing systemic corruption and social mobility constraints. Additionally, the concept of the shadow, both in Balram’s psyche and in the broader socio-political landscape, is explored to understand his inner conflict and moral evolution. The paper also critically contrasts the representation of these archetypes in the novel and its Netflix film adaptation (2021) to analyse shifts in narrative emphasis and visual storytelling. By integrating Jungian archetypal criticism with a comparative media analysis, this research underline how The White Tiger deconstructs conventional hero narratives, challenging the binaries of good and evil, servitude and rebellion, morality and survival.